The enigma of Enaliosuchus, and a reassessment of the Lower Cretaceous fossil record of Metriorhynchidae. (October 2020) - Sachs, Sven; Young, Mark T.; Hornung, Jahn J.
Abstract: Enaliosuchus macrospondylus Koken, 1883 was one of the first thalattosuchian taxa from the Cretaceous to be described. The type series includes an atlas-axis complex, remnants of three post-axial cervical vertebrae, several dorsal vertebrae, a caudal vertebra, an incomplete femur and a fragmentary sacral rib from the upper Valanginian of northern Germany. Additionally, two isolated, non-thalattosuchian, tooth crowns from the uppermost Valanginian to lowermost Hauterivian of different localities in northern Germany were tentatively assigned to E. macrospondylus by Koken. The taxon was established for the distinctive the atlas-axis morphology, in particular the apparent lack of an axis parapophysis. Enaliosuchus macrospondylus has been considered a valid taxon in recent studies, based upon a largely complete metriorhynchid specimen from the Valanginian of France that had been referred to this taxon, an assignment that has never been questioned. Here we provide a detailed re-description of the E. macrospondylus holotype specimen and determine whether it is diagnostic, and if a referral of the French specimen to E. macrospondylus is justified. We also discuss whether E. macrospondylus and another metriorhynchid specimen from the Valanginian of northern Germany, described as Enaliosuchus schroederi, are conspecific. Finally, we provide an overview of the current knowledge of metriorhynchid diversity during the Cretaceous.